Melampolides from Argentinean Acanthospermum australe - Sánchez, Marianela (2009)
The investigation of the ethanol extract of Acanthospermum australe, collected in the province of Misiones, Argentina, yielded eight melampolides (1-8) of the acanthospermal type. Two of them, 8β-hydroxy-9α-(2-methylbutyryloxy)-14-oxo-acanthospermolide (3) and 9α-hydroxy-8β-(2-methylbutyryloxy)-14-oxo-acanthospermolide (7) are new compounds. Two other compounds (4 and 8) have been previously reported, and the NMR data of 4 are corrected. Compounds 1, 2, 5 and 6 have not been previously reported, but are probably artifacts formed during extraction. Compounds 3, 6 and 7 showed slight antibiotic activity against Gram-positive bacteria.